2022
DOI: 10.3389/fimmu.2022.922958
|View full text |Cite
|
Sign up to set email alerts
|

Helios Expression Is Downregulated on CD8+ Treg in Two Mouse Models of Lupus During Disease Progression

Abstract: T-cell–mediated autoimmunity reflects an imbalance in this compartment that is not restored by tolerogenic immune cells, e.g., regulatory T cells or tolerogenic dendritic cells (tolDCs). Although studies into T-cell equilibrium have mainly focused on regulatory CD4+FoxP3+ T cells (CD4+ Tregs), recent findings on the lesser known CD8+ Tregs (CD44+CD122+Ly49+) have highlighted their non-redundant role in regulating lupus-like disease and their regulatory phenotype facilitated by the transcription factor Helios i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Nonetheless, few studies have assessed the relative expression of Helios in specific subpopulations of immune cells beyond simply distinguishing between Helios + and Helios − cells. In this sense, the merits of distinguishing up to three biologically relevant levels of Helios expression is currently being explored (Helios high , Helios mid , and Helios low ) [ 72 , 73 ].…”
Section: Helios In the Immune Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, few studies have assessed the relative expression of Helios in specific subpopulations of immune cells beyond simply distinguishing between Helios + and Helios − cells. In this sense, the merits of distinguishing up to three biologically relevant levels of Helios expression is currently being explored (Helios high , Helios mid , and Helios low ) [ 72 , 73 ].…”
Section: Helios In the Immune Systemmentioning
confidence: 99%
“…From this model, with deficient TGF-β signaling, expression of this cytokine may influence the Helios expressed by CD8 + T cells [ 41 ]. In addition, we found that both the reduction in the proportion of Ly49 + CD8 + T cells and the weaker Helios expression by these cells was correlated to disease progression in two mouse models of lupus (MRL/MPJ and MRL/LPR) [ 73 ].…”
Section: Helios In the Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations